四面楚歌下的同志再现：李碧华和陈凯歌对《霸王别姬》的改写 = Representations of the besieged “Comrade” : Li Bihua's and Chen Kaige's adaptations of the Peking Opera “Farewell My Concubine” - 許维贤 Hee, Wai Siam (2013)
京劇被命名和建構成"國粹",肇始於大清帝國自詡的天下中心在洋槍火炮中被炸毀的歷史性時刻，也是現代性在中國發生的時期。《霸王別姬》原先只是作為一部遲至民國以後才出現的京劇"國粹"劇碼，但其主題承載的國族"自我理想"的"從一而終",卻深深影響了以"霸王別姬"為歷史母題的現代文學作品在20世紀的不斷改編和傳播。《霸王別姬》參與了百年以來國族話語和個人話語的交鋒和協商，而且大多數的改編作品往往到最後都是前者的話語霸權壓倒了後者的聲音。但發展到20 世紀末李碧華和陳凱歌的《霸王別姬》，這兩者之間的話語建構有了重新的博弈和頡頏的可能。國族男性建構轉向中的自戀和殘餘的依戀機制，在這裡微妙發揮了不可小覷的作用。而且這種博弈還多了一層李碧華原著小說的"女性自戀"和陳凱歌電影"男性依戀"的此消彼長。本文細辨原著小說（三個不同版本）和電影的異同，並指出這兩種文本固守在"去歷史化"和"過度歷史化"的兩個極端姿態之餘，如何借"同性愛"說事，最後反而遮蔽了同志四面楚歌的生存窘態。It was at the historical juncture when foreign gunboats shattered the Qing regime’s belief in China as the world’s center that the Peking Opera was picked and named as the quintessential representative of Chinese Culture. The same moment landed China also in the era of modernity. In its wake, Farewell My Concubine, a Republican-era repertoire number, soon substituted itself as an unbending “ego-ideal” for the nation, as seen in various modern literary adaptations up to the late 20th century. In the process, Farewell My Concubine has pitted the nationalist discourse against the non-official ones, with the former often to overwhelm the latter as a result. LiBihua’s and ChenKaige’s adaptations bring in a new round of negotiations and ruse games, in which the nationalist-masculine narcissism and attachment mechanism exert a subtle but significant pull. Still the “feminine narcissism” of Li Bihua’s original novel and the “male attachment” of Chen Kaige’s film manage to play a balancing act. This essay delves into the similarities and differences between Li’s original novel (in three different versions) and the adapted film, and points out, meanwhile, how the two texts have both sharply under-historicized and over-historicized their subject matter by appropriating the “the same-sex love” for their narrative purpose that ends up glossing over the predicaments actual same-sex lovers face in their daily existence.